2015
DOI: 10.1530/ec-14-0132
|View full text |Cite
|
Sign up to set email alerts
|

Short-term efficacy of recombinant human GH therapy in cured acromegaly patients with GH deficiency: a single-center experience

Abstract: The effectiveness and short-term safety of recombinant human GH (r-hGH) in acromegaly patients with GH deficiency (GHD) after treatment are not well established. The study includes ten subjects with acromegaly who had GHD treated with r-hGH for 6 months. Control groups consisted of ten age-, gender-, and BMI-matched healthy subjects and ten active acromegaly patients who were treatment naïve. Body composition, quality of life (QoL), muscle strength, lipid profile, and cardiovascular risk factors were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The coagulopathy is due to thrombin activation. Our previous results have demonstrated that acromegaly patients with GHD who were treated with recombinant GH showed increase activity of plasminogen activator inhibitor-1; however, our study was too short to examine the risk of leukemia [16] .…”
Section: Gh Treatment and Risk Of Leukemiamentioning
confidence: 83%
“…The coagulopathy is due to thrombin activation. Our previous results have demonstrated that acromegaly patients with GHD who were treated with recombinant GH showed increase activity of plasminogen activator inhibitor-1; however, our study was too short to examine the risk of leukemia [16] .…”
Section: Gh Treatment and Risk Of Leukemiamentioning
confidence: 83%
“…Copyright © 2020 Korean Endocrine Society shown to improve IGF-1 concentrations and quality of life without deleterious adverse effects [72,73]. Tritos et al [74], however, warned of increased cardiovascular complications in GH replacement and recommended further investigation on whether it was due to previous GH excess in acromegaly.…”
Section: Precision Therapy and Predictors Of Responsivenessmentioning
confidence: 99%
“…Ku et al [ 71 ] found that the presence of a bilateral pituitary tumor and low immediate post-operative 72-hour GH concentrations (below 0.23 mg/L) predicted GHD. Administration of recombinant GH has been shown to improve IGF-1 concentrations and quality of life without deleterious adverse effects [ 72 , 73 ]. Tritos et al [ 74 ], however, warned of increased cardiovascular complications in GH replacement and recommended further investigation on whether it was due to previous GH excess in acromegaly.…”
Section: Precision Therapy and Predictors Of Responsivenessmentioning
confidence: 99%